Determinants of loan repayment performance of micro and small enterprises: Empirical evidence from Somali Regional State, Ethiopia - Yitbarek Weldegerima Kiros (The Journal of Entrepreneurial Finance (JEF), 2022)
Microfinance Institutions (MFIs) were introduced to reach a large number of active poor people who are excluded from the formal financial institutions due to rigorous collateral requirements. As an instrument of MFIs, Microfinance was introduced to address the financial need of the active poor people. To operate successfully MFIs have to unquestionable ensure that the loan expended to the Micro and Small Enterprises (MSEs) have to be repaid back so as he MFIs can have a financially sustainable and viable operation. In light of this, this research study was conducted to analyze the factors affecting loan repayment of MSEs financed by Somali Microfinance institution by taking lender characteristics in to consideration. Both primary and secondary data was employed. The primary data was collected by distributing questionnaire and through interview. A total of 175 MSEs were selected using purposive sampling technique. The secondary data was acquired from various issues of annual reports of Somali microfinance institution and other concerned institutions. Both descriptive analysis and econometric model, which is, binary logistic regression was employed to analyze the effect of the literature driven variables on loan repayment by MSEs. The econometric model used revealed that among the variables hypothesized to affect loan repayment are loan repayment period, grace period, and timeliness of loan release have statistically significant effect on loan repayment by the MSEs Whereas loan size have statistically insignificant effect on loan repayment by the MSEs.
Keywords: M11; L24; M18; 650; Loan Repayment Performance; MSEs; Logistic Regression; Somali Microfinance; Ethiopia